A control chart for COM-Poisson distribution using a modified EWMA statistic. Issue 18 (12th December 2017) - Aslam, Muhammad; Saghir, Aamir; Ahmad, Liaquat; Jun, Chi-Hyuck; Hussain, Jaffer
ABSTRACT: In this paper, a control chart has been developed for the Conway–Maxwell Poisson (COM-Poisson) distribution using the modified exponentially weighted moving average statistic. The proposed chart provides an efficient detection of smaller changes in the location parameter of the COM-Poisson distribution. The performance of the proposed control chart has been evaluated by the average and the standard deviation of the run length distribution for various parameters. Better detecting ability has also been compared with the existing control chart using EWMA statistic. Using simulation, we also showed the detecting ability over the traditional EWMA chart.